2015
DOI: 10.1051/0004-6361/201425160
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the host galaxy of the short GRB 100628A

Abstract: We report on the results of a comprehensive observing campaign to reveal the host galaxy of the short GRB 100628A. This burst was followed by a faint X-ray afterglow but no optical counterpart was discovered. However, inside the X-ray error circle a potential host galaxy at a redshift of z = 0.102 was soon reported in the literature. If this system is the host, then GRB 100628A was the cosmologically most nearby unambiguous short burst with a measured redshift so far. We used the multi-colour imager GROND at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…The GMOS zeropoints are determined by sources in common with late-time IMACS observations (see below), which are calibrated to a standard star field at a similar airmass. Our limits match the GROND limits reported at δt ≈ 12.2 hr (Nicuesa Guelbenzu et al 2012).…”
Section: Optical/nir Observations and Afterglow Limitssupporting
confidence: 90%
See 2 more Smart Citations
“…The GMOS zeropoints are determined by sources in common with late-time IMACS observations (see below), which are calibrated to a standard star field at a similar airmass. Our limits match the GROND limits reported at δt ≈ 12.2 hr (Nicuesa Guelbenzu et al 2012).…”
Section: Optical/nir Observations and Afterglow Limitssupporting
confidence: 90%
“…S2 and S3 have stellar PSFs, while S1 and S4 have non-stellar PSFs. Previously reported J-band observations also confirm that S2 and S3 are stars (Nicuesa Guelbenzu et al 2012), while S1 and S4 have not been reported in the literature 14 To assess any fading within the XRT position, we obtained a second set of J-band observations at δt = 6.1 hr. Digital image subtraction reveal no residuals to a 3σ limit of J 23.3 mag (Table 2).…”
Section: Optical/nir Observations and Afterglow Limitsmentioning
confidence: 70%
See 1 more Smart Citation